McLeod syndrome: Five new pedigrees with novel mutations. (July 2019) - Weaver, J.; Sarva, H.; Barone, D.; Bobker, S.; Bushara, K.; Hiller, A.; Ishii, M.; Jankovic, J.; Lakhani, S.; Niotis, K.; Scharre, D.W.; Tuite, P.; et al.
Abstract: Objective: To present five new McLeod Syndrome (MLS) pedigrees with novel XK gene mutations, review the literature of this disorder, and discuss the typical and atypical clinical features noted with these new mutations. Methods: This is a multi-center retrospective review of five MLS cases with novel gene mutations. Genotypic and phenotypic information has been obtained from each center. Results: Five novel mutations are reported in this Case series. New clinical findings include prolonged asymptomatic elevated creatine kinase (CK) levels, vocal tics, presence of obstructive sleep apnea (OSA), and one patient of Vietnamese ethnicity. Conclusions: We expand on the clinical and genetic spectrum of MLS demonstrating the clinical variability of MLS. Highlights: Five new mutations for McLeod Syndrome (MLS) are reported in this Case series. Three never-before reported cases of comorbid obstructive sleep apnea are reported. Newly reported Case in Vietnamese ancestry is described. Thirty-year history of asymptomatic hyperCKemia as presenting sign of MLS described.